KESELAMATAN UNIVERSAL DALAM WAHYU 7:1-17 - Meyke Imuly; Monike Hukubun (Program Pascasarjana UKIM, 2019)
Revelation 7: 1-17 give a witness and a vision of the writer of this book about the claim of universal salvation. If it can be viewed in a rhetorical situation, usually the party who opens the communication (speaker / author) tries to convince or influence the listener to accept some specific interpretations or attitudes. That is the reason why an important rhetorical method is used to interpret this text, so that the author's persuasive purposes in this text can be known. Most importantly, when the book of Revelation is understood in the frame of Apocalyptic literature - written in the context of its readers who are experiencing a crisis by various oppressive power pressures, but also the crisis is pleasing with the effort to establish the identity of its beliefs as well as its relevance among the influence of various other different teachings. Thus, the doctrine of universal salvation in the book of Revelation can provide a transformation both for readers of the book of Revelation, but also for readers today who are dealing with issues of identity crisis and relevance.